Decisions and disinformation : an evaluation of the usefulness of the Fast and Frugal Heuristics Programme in uncovering implicature-type disinformation - Potgieter, Burger Gericke (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--Stellenbosch University, 2012.